PRODUCTION PROCESS OF LIQUID FERTILIZER FROM BANANA TRUNK - Suprihatin, Suprihatin (Jurnal Teknik Kimia, 2011)
Banana a plant that many grow in Indonesia. Utilization of banana mostly just takes the fruitand leaves, while the trunk of banana has not been much used. The existence of Ca, P and K in bananatrunk, then the banana trunk can be used as alternative raw material for the production of liquidfertilizer. Produce liquid fertilizer from banana trunk done with the extraction process using a processtemperature of 700C and stirring speed of 240 rpm. Results from the extraction process to analyzelevels of Ca, P and K. Where available Ca content: 16.2% weight, P content: 30.05% weight and Kcontent: 21.5% weight with volume 600 ml of solvent and 15 minutes of stirring time.Key words: banana, liquid fertilizer, extraction. , alternative fertilizer